Penapisan dan Karakterisasi Rhizobakteria serta Uji Aktivitasnya dalam Mendukung Perkecambahan dan Pertumbuhan Benih Jagung (Zea mays L.) - Agustiyani, Dwi (Perhimpunan Biologi Indonesia, 2016)
ABSTRACTPlant Growth Promoting Rhizobacteria (PGPR) are a group of bacteria known to influence plant growth by direct or indirect mechanisms. In search of efficient PGPR which potential as biofertilizers, a total of 26 isolates of rhizobacteria were isolated from various plant rhizosphere. These 26 isolates were screened through in vitro methods for PGPR properties like phosphate solubilization, siderophore, IAA and amonia production, and catalase activity. The result revealed that 9 isolates showed positive activities for phosphate solubilization 17 isolates for IAA production 18 isolates for siderophores 19 isolates for ammonia production and all of the isolates have catalase activities . Only four isolates (Az.KT.CSC, Az.D.8B, Az.D.8A and Az.Lo.10B) exhibited multiple plant growth promoting traits viz., phosphate solubilization, siderophore, IAA, amonia production, and catalase activity. Ten isolates that have different characters were further investigated for quantitative analysis of IAA production, HCN production and its effect on germination and seedling growth of Zea mays. The range of IAA production was 3,12â 134,27 ppm, among ten isolates, Az.D.8B isolate produced the highest IAA (134,27 ppm). Production of HCN was detected in eight isolates. Four isolates positively affected the germination of Zea mays seeds. Highest root elongation was recorded when seeds were treated with Az.Lo.5 isolate. Whereas, the highest chlorophyl content and plant high were recorded when seeds were treated with Az.B.8B isolate.Keywords: N-fixing bacteria, PGPR, IAA, siderophore, catalase